Perineorrhaphy Outcomes Related to Body Imagery: A Randomized Trial of Body Image Perception. Issue 5 (26th May 2021) - Ninivaggio, Cara S.; Komesu, Yuko M.; Jeppson, Peter C.; Cichowski, Sara B.; Qualls, Clifford; Qeadan, Fares; Rogers, Rebecca G.; Dunivan, Gena C.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: The aim of this study was to determine if a perineorrhaphy at the time of apical pelvic organ prolapse surgery positively affects women's body image. Methods: This is a randomized controlled trial of women undergoing apical suspension procedures in which women (GH ≥2 cm to ≤6 cm) received either perineorrhaphy or no perineorrhaphy. The primary aim compared body image between the groups postoperatively using the Body Image in Pelvic Organ Prolapse (BIPOP) questionnaire. Secondary outcomes included prolapse stage, pain, pelvic floor muscle strength, pelvic floor symptoms, and sexual function. Between- and within-group differences were compared using Fisher exact test for categorical variables and t tests for continuous variables. When continuous variables were not normally distributed, the Welch-Satterthwaite test was used. Within-group analyses were performed via paired t tests for select continuous variables. Results: Forty-six women were enrolled; 45 (97.8%) completed the 6-week assessment and 38 (82.6%) completed the 3-month assessment. There were no differences in baseline characteristics. Although women within groups had an expected improvement in mean Body Image in Pelvic Organ Prolapse and subscale scores between baseline and 3 months ( P < 0.05), there were no differences in the mean scores between groups. In addition, there were no differences between groups in any of the secondary outcomes. Conclusions: Performance of apical prolapse surgery improved women's body image, irrespective of performance of a perineorrhaphy. Other important outcomes, including pain, did not differ between women in the 2 groups. These findings demonstrate the need for further trials to investigate the utility of this procedure.